ETOS BISNIS ETNIS MADURA PERANTAUAN DI KOTA MALANG: MEMAHAMI DIALEKTIKA AGAMA DENGAN KEARIFAN LOKAL - Djakfar, Muhammad (Fakultas Ekonomi, UIN Maliki Malang, 2011)
The Madurese ethnic is known as one of the diverse ethnic groups in Indonesia for having a high business ethic. The only question is whether their business ethic due to religious factors, environmental values which forced them to work hard or because of both factors as a result of the dialectical process that eventually forms the Madurese ethnic. Therefore, this true of academic question is to be understood in this study. The object of this study is Madurese ethnic who live in Malang, both from santri and non-santri. The research uses a qualitative approach with a phenomenological and descriptive analysis method. Data mining techniques include observation, interviews, and documentation. The results show that the dialect that has occurred gradually in a relatively long time formed the Madurese ethnic in the city of Malang as a hard worker. It indicates that both santri and non-santri are not separated because motivated by religious teachings and moral values that exist locally. However, the santri groups seem more motivated by religious teachings compare with non-santri groups which more motivated by local wisdom value.